Impact of the Swimming Practice on the Postural Balance among Tunisian Athletes - Sioud, Rim; Amara, Sofiene; Gaied-Chortane, Sabri; Khalifa, Riadh (Advances in Social Sciences Research Journal, 2023)
Our Study aims were to test the impact of swimming practice on the development of postural stability among Tunisian Athletes. The analyses deal with the impact of the practice of swimming on the postural balance. They clarify the various constraints that influence the control mechanisms involved in maintaining the balance in the resort standing. Our study addresses 20 same age category male subjects (senior) returned in: an experimental group (10 swimmers, belonging to the Tunisian national team) and a control (no sports group 10). For this study we used the Neurocom version 8.0.2 system: scale Master® consisting of a flat form of force connected to a string of data to measure the speed of oscillation of the center of pressure in strong support bipedal, eyes open on ground. The results obtained showed no direct effect of the swimming practice on postural stability of Tunisian athletes. In fact swimming poses the need to evolve in an environment different from that in which any subject has built his balance, his motor skills of every day, the latter two are insured through the muscles; so balance follows the permanent integration of information transmitted by three receiving systems: Visual, proprioceptive and vestibular.